(untitled) (Research, Society and Development, 2021)
This bibliographical work, in article format, presents in its writings some educational conceptions regarding playfulness in early childhood education in an inclusive way. Therefore, it is anchored in the theoretical foundations of some authors, such as: Almeida (1974); Barbosa (2006); Bossa (2007); Medeiros (2000); Negrini (1994); Piaget (1979); Ramos (2011); Rojas (2006); Velasco (2006); Rego (2011); Café (2018), Lyra (2019); Ferreira (2020), in addition to legal documents and educational and other theoretical guidelines, which in their studies contribute to the discussions established here. The article under study has a general objective which is to analyze the role of the teacher in early childhood education through playfulness in educational establishments in an inclusive way. The work is justified by the need to present in the academic environment productions that deal with the theme addressed by the title of the work. Methodologically, we will make use of a qualitative approach, with a bibliographic character, supported by secondary sources of information. In this educational link, playfulness is understood as a multifaceted process of learning development, which requires at all times a didactic involvement full of diversified activities, in addition to children’s games and games from the perspective of educating, caring and playing.